Ulama dalam Perspektif Nahdlatul Ulama - Romzi, Moh. (Religió: Jurnal Studi Agama-agama, 2012)
The majority of Muslim believes that the Prophet Mohammad is not only a religious leader but also a political leader. Besides excluding policy and order in terms of state and people’ problem, he also produces religious instructions related to religion. This condition also prevails in the era of caliphate or Khulafa’ur Rasyidin. At the end of both periods prophet and caliphate, dual function of leadership was disintegrated, the role of state leadership is authorized by caliphate or ‘Umarâ while religious leader by ‘Ulamâ. After the Prophet’s time, the Caliphate could not appropriately perform the Prophet’s role, in both of mentioned forms. Following the period of ‘Alî ibn Abî T{âlib, Islamic state has separated religious affairs from bureaucratic entities: between religion and state. It has eventually created a clash. Religious orders and state regulations are sometimes contending and contradicting. It can be seen from the role of ‘ulamâ in dealing with ‘umarâ that contradict with sharia or general people’ interest. Somehow they contradict each other but also go in cooperation. There is ‘ulamâ who is explicitly advising and challenging the ‘umarâ but also otherwise. This article aims to explain and analyze definition and interpretation of Islamic leader (ulamâ) from Qur’anic and Hadith perspective. In addition, this article will also describe definition and role of Islamic leader using Nahdlatul Ulama’s perspective.